Polymorphism in the bovine BOLA-DRB3 upstream regulatory regions detected through PCR-SSCP and DNA sequencing - Ripoli, María Verónica (2004)
In the present work, we describe through polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) and DNA sequencing the polymorphism within the URR-BoLA-DRB3 in 15 cattle breeds. In total, seven PCR-SSCP defined alleles were detected. The alignment of studied sequences showed six polymorphic sites (four transitions, one transversion and one deletion) in the interconsensus regions of the BoLA-DRB3 upstream regulatory region (URR), while the consensus boxes were invariant. Five out of six detected polymorphic sites were of one nucleotide substitution in the interconsensus regions. It is expected that these mutations do not affect significantly the level of expression. In contrast, the deletion observed in the sequence AY364455 between CCAAT and TATA boxes could have some effect on affinity interactions between the promoter region and the transcription factors. The URR-BoLA-DRB3 DNA analyzed sequences showed moderate level of nucleotide diversity, high level of identity among them and were grouped in the same clade in the phylogenetic tree. In addition, the phylogenetic tree, the similarity analysis and the sequence structure confirmed that the fragment analyzed in this study corresponds to the URR-BoLA-DRB3. The functional role of the observed polymorphic sites among the regulatory motifs in bovine needs to be analyzed and confirmed by means of gene expression assays.